2016
DOI: 10.26481/marble.2014.v2.308
|View full text |Cite
|
Sign up to set email alerts
|

Chordoma and its embryonic determinants

Abstract: Background. Chordomas are rare malignant tumors occurring along the axial skeleton

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A recent study showed that, other than Brachyury, another embryonic transcription factor like Twist might have a role in the tumorigenesis of chordoma (Vanderheijden, 2014). Therefore, we conducted the present study to investigate the possible role of Twist in cell migration of chordoma cells and its role in metastasis.…”
Section: Introductionmentioning
confidence: 95%
“…A recent study showed that, other than Brachyury, another embryonic transcription factor like Twist might have a role in the tumorigenesis of chordoma (Vanderheijden, 2014). Therefore, we conducted the present study to investigate the possible role of Twist in cell migration of chordoma cells and its role in metastasis.…”
Section: Introductionmentioning
confidence: 95%